Biocompatibilidad del cianoacrilato de butilo en suturas en piel en comparación con las suturas convencionales - Cáceres Barreno, Andrés (2013)
ABSTRACT Introduction: N-Butyl-cyanoacrylate is a tissue-synthesis material. It offers countless advantages: short application time, easy execution, as well as possessing hemostatic character. This material is bacteriostatic, biodegradable, and exhibits suitable tensile strength. Objective: The objective of the present paper was the histological evaluation of n-butyl-cyanoacrylate biocompatibility on rats dorsum (spine), compared to braided black silk and Polyglactin 910. Materials and Methods: Thirty six Wixtar albino rats were used for the procedure. They were randomly divided into four groups (A, B, C, D) related to the time of sacrifice (3rd, 7th, 14th and 21st day) respectively. On the rats' spine, three 2 cm long incisions were performed. Histological parameters were as follows: polymorphonuclear cell inflammatory infiltrate, young fibroblasts and epidermis thickening. Results: N-butyl-cyanoacrylate caused lesser polymorphonuclear infiltrate when compared to other used materials. Fibroblast proliferation peaked in groups treated with n-butyl-cyanoacrylate when compared to the rest. Epidermis thickening showed high mitotic ability of keratocytes to remodel epithelium. At the 14th and 21st days most tissues treated with N-Butyl-cyanoacrylate were found to be completely remodeled when compared to the rest. Conclusion: N-butyl-cyanoacrylate was shown to be the most biocompatible material, since it elicited shortest healing time.